CryoEM structures of anion exchanger 1 capture multiple states of inward- and outward-facing conformations - Hristina R. Zhekova; Jiansen Jiang; Weiguang Wang; Kirill Tsirulnikov; Gülru Kayık; Hanif Muhammad Khan; Rustam Azimov; Natalia Abuladze; Liyo Kao; Debbie Newman; Sergei Yu. Noskov; D. Peter Tieleman; et al. (Communications Biology, 2022)
CryoEM structures and computational modeling of bovine anion exchanger 1 in both inward and outward facing conformations reveal an elevator-like mechanism of ion transport by a solute carrier ion transport family 4 member.